2019
DOI: 10.1037/sgd0000312
|View full text |Cite
|
Sign up to set email alerts
|

Bisexual women’s reports of descriptive drinking norms for heterosexual, bisexual, and lesbian women.

Abstract: Bisexual women drink more than lesbian and heterosexual women. However, few studies have examined factors that influence drinking among bisexual women. Although descriptive drinking norms are strong predictors of drinking, little research has examined how drinking norms influence alcohol use for bisexual women. The present study examined bisexual women’s reports of descriptive drinking norms for bisexual, lesbian, and heterosexual women and associations with their own frequency of alcohol consumption, quantity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…A recent study examining bisexual women's alcohol use and descriptive drinking norms found that bisexual women believe that other bisexual women drink more than lesbian women. 48 Moreover, bisexual women's frequency of alcohol consumption, number of binge drinking episodes, and hazardous alcohol use as measured by AUDIT were significantly associated with these descriptive drinking norms for bisexual women, but not descriptive drinking norms for lesbian or heterosexual women. 48 In addition, a previous study has shown that both heterosexual and lesbian/gay individuals hold negative attitudes toward bisexual individuals such as beliefs about hypersexuality, immorality, and being confused about one's sexuality.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A recent study examining bisexual women's alcohol use and descriptive drinking norms found that bisexual women believe that other bisexual women drink more than lesbian women. 48 Moreover, bisexual women's frequency of alcohol consumption, number of binge drinking episodes, and hazardous alcohol use as measured by AUDIT were significantly associated with these descriptive drinking norms for bisexual women, but not descriptive drinking norms for lesbian or heterosexual women. 48 In addition, a previous study has shown that both heterosexual and lesbian/gay individuals hold negative attitudes toward bisexual individuals such as beliefs about hypersexuality, immorality, and being confused about one's sexuality.…”
Section: Discussionmentioning
confidence: 86%
“…48 Moreover, bisexual women's frequency of alcohol consumption, number of binge drinking episodes, and hazardous alcohol use as measured by AUDIT were significantly associated with these descriptive drinking norms for bisexual women, but not descriptive drinking norms for lesbian or heterosexual women. 48 In addition, a previous study has shown that both heterosexual and lesbian/gay individuals hold negative attitudes toward bisexual individuals such as beliefs about hypersexuality, immorality, and being confused about one's sexuality. 49 A 2016 study with a nationally representative sample of U.S. adults found that, since the passage of marriage equality, while attitudes toward lesbian women and gay men were becoming more positive, most adults had neutral or negative attitudes about bisexual individuals.…”
Section: Discussionmentioning
confidence: 86%
“…For example, a prospective survey study investigating relationships between perceived descriptive drinking norms and alcohol use among heterosexual, lesbian, and bisexual women found that sexual minority women consistently perceived the “typical sexual minority woman” to consume more alcohol than “the typical woman” across four assessment points (Litt, Lewis, Rhew, Hodge, & Kaysen, 2015). Further, sexual minority-specific descriptive peer norms were stronger positive predictors of lesbian and bisexual women’s future drinking than were less specific norms for the “typical woman.” In another recent study, Ehlke, Stamates, Kelley, and Braitman (2019) recruited a sample of bisexual women and separately assessed participants’ perceived drinking norms for bisexual, heterosexual, lesbian, and bisexual women. Underscoring the importance of reference group specificity and sexual minority social identity, perceived bisexual drinking norms were most strongly related to bisexual participants’ own alcohol consumption while perceived heterosexual drinking norms were negatively associated with participants’ drinking.…”
Section: Resultsmentioning
confidence: 99%
“…A general trend observed among the studies reviewed at the perceived and actual norm levels of analysis was that intervention implications associated with findings were either not articulated or rarely went beyond a broad statement about the potential utility of norms-based interventions (for valuable exceptions see Ehlke et al, 2019 and Litt et al, 2015). To better inform future research and intervention development, a second, increasingly focused generation of norms-focused research with sexual minorities should ensure that operationalizations of norms, assessment methods, reference groups, and discussions of findings more clearly map onto a specific level of analysis and follow from social psychological theories of normative influence.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, masculine-presenting SMW might engage in problematic drug use given that this behavior might be consistent with their masculine presentation (Rosario et al, 2008). Other factors that were not captured in the current study, such as social context, pressure to drink, connection to other SMW, and perception of drinking norms in the community, represent important motives underlying SMW’s alcohol use (Condit et al, 2011; Ehlke et al, 2019; Lee et al, 2016). As such, future studies should examine these factors in relation to sexism and SMW’s mental and behavioral health.…”
Section: Discussionmentioning
confidence: 97%